Using IFS as an Encryption Method - Al-Saidi, N.M.G.; Rushdan, M.S. (2009 International Conference on Education Technology and Computer, 2009)
Encryption is the process of rearrange the message into difference form so that the message is keep secret The IFS is a scheme for describing and manipulating complex fractal attractors using simple mathematical models. More precisely, the most popular "fractal -based" algorithms for both representation as well as compression of computer images have involved some implementation of the method of Iterated Function Systems (IFS) on complete metric spaces. Fractals are generated by simple, recursive calculations. This paper proposes a novel encryption method based on the theory of iterated function system (IFS). This approach exploits the main feature of fractals generated by IFS, so that any individual that happens to find the transformed message will not be able to understand it without the correct method that will reverse the transformation, usually through some contact/agreement with the original.